INOVASI TEKNOLOGI PAKAN UNTUK MENINGKATKAN PRODUKSI SUSU DADIH KERBAU MURRAH DI KECAMATAN TILATANG KAMANG KABUPATEN AGAM - Elihasridas Elihasridas; Elly Roza; Salam N. Aritonang; Yulia Yellita; Ade Rakhmadi; Rizqan Rizqan (Jurnal Hilirisasi IPTEKS, 2022)
This activity aims to increase buffalo milk production by improving feed management through the application of science and technology will lead to an increase in the income of Murrah buffalo breeders. This program is conducted to the Kelok Rambai livestock Group, Kapau, Tilatang Kamang District, Agam Regency. This farmer group received assistance from the provincial government of West Sumatra, 15 Murrah buffaloes as milk producers, where the milk produced is fermented into curd. The pattern of maintenance is semi-intensive and the feed provided is inadequate both in quantity and quality and the lack of knowledge of farmers so that the productivity of buffaloes is still low. The method of activities carried out in this service is participatory community empowerment including counseling, training, guidance, discussion and evaluation/monitoring. The training/pilot of feed technology introduced is multi-nutrient feed supplement, namely Urea Saka Blok, and ammoniated rice straw as a quality fiber feed ingredient. In addition, the cultivation of legume feed is indigofera plants which can be used as green concentrate because high protein content. The results of using ammoniated rice straw supplemented with Urea Saka Blok in buffaloes increased feed consumption significantly from an average of 2.5% to 2.75% of body weight or an increase of 0.25%. This increase in feed consumption has implications for milk production which was initially 2 liters per day, increased to 3 liters per day or an increase of about 50%, and what is quite interesting is that until the 10th month of lactation milk production is still 3 liters per day. It is hoped that the community service activities at the Kelok Rambai Cattle Farmer Group can increase the income of group members, apply good maintenance management, increase motivation, apply sustainable introduced feed technology and make Nagari Kapau as one of the centers for Murrah buffalo farming producing milk/curd. in West Sumatra.